Corpus approaches to social media - Rüdiger, Sofia; Dayter, Daria (Studies in corpus linguistics, 2020)
"From Twitter to Reddit, Facebook, and WhatsApp - social media is a part of modern everyday life. Studying the language used on social media platforms presents great opportunities as well as challenges to corpus linguists. The contributions in Corpus Approaches to Social Media address technical, ethical, and methodological issues by showcasing in-depth social media studies as conducted by corpus scholars. The chapters are based on a variety of social media platforms and include corpus perspectives on the language of online communities, linguistic variation in short media texts, and the role of images in computer-mediated communication. A particularly strong point of the collection are the detailed accounts of the methodological aspects of working with social media corpora. The volume features research applying traditional corpus linguistic methods to social media data as well as novel and innovative research methods for the analysis of multimodal material and atypical corpus texts"--